Facilitators and barriers of infectious waste management practice in public and private health facilities of Addis Ababa, Ethiopia: a qualitative phenomenological study - Berhe, Trhas Tadesse; Feleke, Alemu Kibiret; Bekele, Getabalew Endazinaw; Gebrihiwot, Ephriam Mamo; Ali, Yimer Hussien; Tedila, Getachew Woldeyohaness (Frontiers in Public Health, 2025)
BackgroundManagement of infectious waste is essential to address health risks to healthcare workers, patients, and the public. Healthcare facilities, especially in resource-poor settings, however, face significant challenges in effectively and safely handling infectious waste.ObjectiveThis study is aimed to explore the barriers, and facilitators, infectious waste management in private and public health facilities to inform policy and practice improvement.MethodsA qualitative study employed a descriptive phenomenological design was used in a public and private health facilities in Addis Ababa, Ethiopia from November 30 to December 30, 2023. Data were collected through 16 key informant interviews and 12 focus group discussions with the health care providers, waste management staff, and other stakeholder involved in infectious healthcare waste management. Participants were purposively selected based on their roles in infectious waste management. All interviews and discussions were audio recorded, transcribed verbatim and analyzed thematically using ATLAS.ti software.ResultsSeveral barriers to effective infectious waste management were identified, including lack of strategic planning, inadequate financial resources, poor infrastructure, and limited training opportunities. Insufficient waste segregation facilities, shortages of specialized waste containers, and irregular waste collection services further hindered proper waste disposal. Facilitators included strong institutional support, targeted training programs, monitoring mechanisms (e.g., waste audits), and reliable disposal services. Motivators for improving waste management included greater stakeholder engagement, financial investment, and integration of waste management into broader healthcare policies.ConclusionAddressing financial constraints, improving training programs, strengthening infrastructure, and fostering stakeholder collaboration were critical for enhancing infectious waste management in healthcare settings. The study highlighted the need for strategic planning, policy revision, and sustained investments to ensure sustainable and safe infectious waste disposal practices.